Polysomnography for the sleep technologist : instrumentation, monitoring, and related procedures - Robertson, Bonnie (Polysomnographic technologist); Marshall, Buddy; Carno, Margaret-Ann (St. Louis, Missouri : Elsevier, 2014)
The only sleep technology text written by experienced polysomnography educators, this book covers the procedural knowledge you need to understand sleep studies. A sequential learning model systematically covers electronics, instrumentation, recording parameters, data acquisition, ancillary equipment, troubleshooting, recording quality, infection control, basic positive pressure therapy, and cardiopulmonary monitoring and intervention essential to polysomnography.
Overview of sleep medicine physiology and technology -- Classification of sleep disorders -- Electronics and electricity -- Frequency, voltage, and morphology of signals -- Bioelectric signals of interest in sleep medicine -- The recording of physiological parameters and electrical safety -- Data acquisition systems -- Sensors, transducers, and ancillary equipment -- The polysomnogram : prestudy procedures, monitoring activities, and poststudy scoring and interpretation -- Recognizing, evaluating, and minimizing recording artifacts -- The cardiopulmonary system : essentials for the polysomnographic technologist -- Noninvasive monitoring of gas exchange during testing -- Diagnosis, treatment, and outcome management of sleep-disordered breathing -- Infection control and emergent response in the sleep center.
Includes bibliographical references and index.
Keywords: Polysomnography; Sleep disorders; Polysomnography -- instrumentation; Polysomnography -- methods; Sleep Wake Disorders